Dynamic navigation guided surgery and prosthetics for immediate loading of complete‐arch restoration. Issue 1 (19th January 2021) - Pozzi, Alessandro; Hansson, Lars; Carosi, Paolo; Arcuri, Lorenzo
Abstract: Objective: To assess clinical and radiological performance of novel digital workflow integrating dynamic guided surgery, to streamline execution of implant placement, soft and bone tissue sculpturing, and immediate delivery of navigation guided complete‐arch prosthesis. Materials and Methods: This proof of concept prospective single cohort study investigated 10 consecutive patients (three males, seven females; mean age 62.5 ± 8.9 years; range, 48–75) requiring at least one complete‐arch fixed dental prostheses (FDP) in both jaws, treated between January and August 2019. Primary outcomes were implant and prosthetic success rates, surgical and prosthetic complications. Secondary outcomes were marginal bone loss (MBL), implant stability quotient (ISQ), periodontal parameters (plaque and bleeding indexes). Results: Sixty implants (32 NobelParallel TiUltra and 28 NobelActive TiUltra, Nobel Biocare) were placed and 14 complete‐arch FDPs immediately loaded (mean follow‐up 16.2 ± 1.7 months, 14–18). One implant failed and was immediately replaced. No other surgical or biological complications occurred, accounting for a cumulative success rate of 98.3%. No prosthetic complication occurred, leading to 100% prosthetic success rate. Mean ISQ at implant placement was 71 ± 2.8 (65–78). The mean MBL was −0.53 ± 0.28 mm (−0.22 to −1.12 mm). Plaque and bleeding scores were 14.4 ± 8.18 and 7.15 ± 4.4, respectively. Conclusion: Within the limitations of this proof‐of‐concept dynamic navigation was effective to deliver in the planned coordinates both implants and prosthesis and guide bone and soft tissue sculpturing. Immediate loading of digitally prefabricated esthetically driven complete‐arch FDP was facilitated, resulting in high implant and prosthetic success rates. Clinical Significance: The investigated digital workflow integrating dynamic navigation may overcome the difficulties related to immediate positioning and loading of digitally prefabricated complete‐arch FDP. The navigation guided soft and bone tissues sculpturing, associated to xenogeneic collagen matrix grafting, represented a predictable technique to achieve the digitally planned interface, reestablishing the mucosal dimension required for the protection of underlying bone while maintaining tissue health.